2007
DOI: 10.1111/j.1475-2743.2006.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of a nitrification inhibitor, dicyandiamide, in reducing nitrous oxide emissions in four different soils under different climatic and management conditions

Abstract: Nitrous oxide (N 2 O) is a potent greenhouse gas and, in New Zealand, about one-third of the total greenhouse gas emissions from the agricultural sector are of N 2 O, mostly derived from animal excreta in grazed pasture soils. The aim of this study was to determine the effectiveness of a nitrification inhibitor, dicyandiamide (DCD), in reducing N 2 O emissions from animal urine patches in four different soils located in different regions of New Zealand with different soil, climatic and management conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
105
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 15 publications
13
105
0
3
Order By: Relevance
“…Fertilisers coated with nitrification inhibitor have been shown to be effective in reducing nitrification, and N 2 O emissions by up to~80%, as reviewed by (de Klein et al 2001). Applied as a spray, nitrification inhibitors can also be effective in reducing N 2 O emissions from animal urine by 27-91%, with pasture yield increases of 0-36%, depending on the magnitude of N loss (Di et al 2007;Kelly et al 2008;Smith et al 2008). However, many of these studies have been conducted under optimal conditions for N 2 O production and over short periods, so the potential on-farm abatement is likely to be more conservative than the published data.…”
Section: Nitrous Oxidementioning
confidence: 99%
“…Fertilisers coated with nitrification inhibitor have been shown to be effective in reducing nitrification, and N 2 O emissions by up to~80%, as reviewed by (de Klein et al 2001). Applied as a spray, nitrification inhibitors can also be effective in reducing N 2 O emissions from animal urine by 27-91%, with pasture yield increases of 0-36%, depending on the magnitude of N loss (Di et al 2007;Kelly et al 2008;Smith et al 2008). However, many of these studies have been conducted under optimal conditions for N 2 O production and over short periods, so the potential on-farm abatement is likely to be more conservative than the published data.…”
Section: Nitrous Oxidementioning
confidence: 99%
“…In the nutrient solution nitrification inhibitor, dicyandiamide (DCD, C 2 H 4 N 4 ), were used to avoid NH 4 ? converted rapidly to nitrate (NO 3 -) (O'Callaghan et al 2010), while the nitrification inhibitors could perform the denitrification efficiently (Di et al 2007;Monaghan et al 2009). Thus, the ammonium and nitrate could co-exist with little or no conversion.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…To compensate for these limitations, researchers have investigated complementary N mitigation techniques, such as blocking NH þ 4 oxidation to NO À 3 using nitrification inhibitors (Yu et al, 2007;Watson et al, 2009). Studies have revealed that the inhibitory potential of dicyandiamide (DCD) can curb nitrate leaching by up to 76% (Di and Cameron, 2004) and N 2 O emissions by up to 70% (Di et al, 2007). Yet for all its effectiveness, degradation in soil limits the persistence of DCD (Estermaier et al, 1992), which has a half-life estimated between 110 d at 5°C and approximately 20 d at 25°C (Kelliher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%